SISTEM PENGELOLAAN REKAM MEDIS DI PUSKESMAS BAURENO - Mitha Amelia Rahmawati; Sukma Lathifa El-syafa'ah; Vannesa Mae (MAINTEKKES : The Journal of Management Information and Health Technology, 2023)
The management of medical records at public health center is to support the achievement of orderly administration in order to achieve the objectives of the public health center, namely to improve the quality of health services. Based on the results of the preliminary study, several problems were found at the Baureno public health center which were less effective, namely the management of medical records was not in accordance with the work procedures and organization of health care facilities. This can be seen from the lack of medical record human resources, frequent duplication of medical record numbers, use of tracers that are not optimal, often late in reporting medical records, lack of effective communication that occurs between medical record officers and other officers at public health center. The purpose of this study was to determine the medical record management system at the Baureno public health center. The results of the study found that the medical record management system for the Baureno public health center, including for SP2TP, was still not suitable due to a lack of coordination in each part of the public health center so that delays often occurred, the medical record service system was in accordance with the SPM, namely from registration to the patient's discharge, the patient's medical record was always complete. as well as on time. The medical record processing system which consists of TPP, assembling, indexing, coding, and filling has been running according to the SOP. The medical record management process at public health center must continue to improve and maintain an appropriate medical record management system to support the achievement of an effective and efficient medical record administration order.